BATASAN KEPENTINGAN UMUM DALAM MENERAPKAN DEPONERING DIKAITKAN DENGAN KEWENANGAN JAKSA AGUNG REPUBLIK INDONESIA DALAM MELAKUKAN PENYAMPINGAN PERKARA DEMI KEPENTINGAN UMUM - Dian Maria Ciristin Simbolon; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Law No. 16 of 2004 on the Attorney RI and explanation says aside the case (deponering) the public interest (Article 35 sub c) are as follows: does "public interest" is the interests of the nation and / or the public interest. Leaving aside the matter referred to in this provision is an implementation of the principle of opportunity, can only be carried out by the Attorney General after considering the advice and opinions of the bodies of state power that have a relationship with these problems. The purpose of writing the thesis as follows: first, to find out what are the limits of public interest in applying deponering associated with the authority of the Attorney General in conducting the case aside for the sake of public interest. Second, to find out the settings of opportunity principle in the Act No. 16 of 2004 on the Prosecutor of the Republic of Indonesia.This type of research can be classified normative law research,descriptive study, a study that illustrates clearl of they and in detail about restrictions in the public interest in implementing depenering associated with the authority of attorney general Republic Indonesia in doing case in thepublic interest. Source data used are secondary data consist of primary legal materials, secondary law, and tertiary legal materials, data collectton techniques in this study with a literature study method, after the data is co.llected and analyzed to be decudedFrom the results of research and discussion can be concluded first that, authority of the Attorney General to exclude matters of public interest are not clear boundaries or parameters that are of public interest, so that the necessary arrangements are clear and limited the restrictions / criteria of public interest. Second, based on the explanation of Article 77 of the Criminal Procedure Code, the manual implementation of the Criminal Code, Criminal Procedure Code recognizes the existence of the embodiment of the principle of opportunity, but the Criminal Code does not regulate in detail the problem aside the case. deponering setting is found in Article 35 letter c of Law Number 16 of 2004 on the Prosecutor of the Republic of Indonesia which states that the Attorney General has the authority to set aside the case in the public interest as the interests of the nation.Keywords: Principles - Opportunity - Deponering - For the Public Interest